The position and authority of the business competition supervisory commission (KPPU) in supervising business competition in Indonesia - Muhammad Zulfadli; Rasyid Ridha; Syarifah Balkis; Muh. Said (Technium Social Sciences Journal, 2023)
This article reviews the KPPU’s position as an institution in the constitutional system of the Republic of Indonesia and examines in more depth the concept of strengthening the KPPU’s authority in supervising and enforcing business competition law in Indonesia. Institutional status is very important because the KPPU is expected to be able to work together quickly in accordance with the mandate of the law. No. 5 of 1999. Strengthening the commission must be followed by increasing the effectiveness of the commission’s function so that it is not only a provider of recommendations; and organize its relations with other state institutions to emphasize the ideals of a rule of law as well as the modern principle of separation of power and the basic concept of mutual control-mutual balance.